2014
DOI: 10.1177/2048872614534079
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following primary percutaneous coronary intervention in the setting of cardiac arrest: A registry database study

Abstract: In conclusion, in-hospital mortality remains high among patients undergoing PPCI in the context of CA, particularly among those that arrest prior to ambulance arrival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Out of hospital cardiac arrest associated with acute myocardial infarction (MI) occurs in 8% to 10% of acute MI patients . Although there have been significant improvements in outcomes, patients with cardiac arrest continue to have a high‐mortality despite aggressive treatment, including frequent use of urgent revascularization …”
Section: Introductionmentioning
confidence: 99%
“…Out of hospital cardiac arrest associated with acute myocardial infarction (MI) occurs in 8% to 10% of acute MI patients . Although there have been significant improvements in outcomes, patients with cardiac arrest continue to have a high‐mortality despite aggressive treatment, including frequent use of urgent revascularization …”
Section: Introductionmentioning
confidence: 99%
“…The Kunadian et al study and the Dumas et al studies are both retrospective studies examining the utilization of PCI for OHCA in United Kingdom and Parisian population respectively [1] [3]. The current study examined a large cohort of OHCA patients from the Nationwide Inpatient Service (NIS) database to compare demographic and clinical differences between those who received PCI and those who did not, and the impact of PCI on survival.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Registry of Acute Coronary Events (GRACE) Registry found that cardiac arrest was an independent prognostic factor for in-hospital mortality [3] [7]. Despite advancements in resuscitation guidelines and techniques, survival rates remain low for both OHCA (9.5%) and IHCA (23.9%) [3] [6] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations